The Predictive Role of Innovation Management with Lifelong Learning on Individual Innovativeness: An Examination on Teachers - EKŞİ, HALİL (HIPATIA PRESS, 2021)
The purpose of this study is to analyze the relationships among innovation management competencies of school administrators, teachers' lifelong learning tendencies, and individual innovativeness levels of teachers and to determine the predictive value of innovation management competencies of school administrators and teachers' lifelong learning tendencies have on their individual innovativeness levels. The sample of the study consist of 302 teachers from 38 public schools in Gungoren province of Istanbul city. A relational survey model has been used and the data have been obtained utilizing three scales: Innovation Management Scale in Schools, Individual Innovativeness Scale, and Lifelong Learning Tendency Scale. The data have been analyzed using correlation and regression analyses. According to the research results, a positive correlation has been found among perceived innovation management competencies of school administrators, teachers' lifelong learning tendencies, and individual innovativeness levels of teachers. It has been determined that perceived school administrators 'innovation management competencies predicted teachers' individual innovation levels by 5% and lifelong learning tendencies of teachers by 3%. Teachers' lifelong learning tendencies predicted their individual innovativeness level by 17%. Besides, perceived school administrators 'innovation management competencies and lifelong learning tendencies of teachers have been determined to explain 19 % of the variance in the individual innovativeness level of teachers. This effect size is medium.
Keywords: Innovation; Innovation Management; Individual Innovativeness; Lifelong Learning